Inverse effect in simultaneous thermal and radiation aging of EVA insulation - G. Przybytniak; J. Boguski; V. Placek; L. Verardi; D. Fabiani; E. Linde; U. W. Gedde (eXPRESS Polymer Letters)
Poly(ethylene-co-vinyl acetate) (EVA) insulation of the cable applied in nuclear power plants was accelerated aged by gamma-rays at two various temperatures, namely 55 and 85°C. Radiation degradation in the dose range of 0–1500 kGy was monitored using a Differential Scanning Calorimetry method by measuring oxidative induction temperature (OITp), gel fraction, mechanical and electrical tests. It was confirmed that a dose rate effect in the range of 420–1500 Gy/h was negligible whereas progress of degradation with increasing dose was strongly temperature dependent. For the insulation accelerated aged at 85°C the OITp and permittivity measurements confirmed lower degradation than for the specimens radiation treated at 55°C at the same dose rates. It was postulated that an inverse thermal effect resulted from radiation induced cross-linking facilitated by melting of EVA crystallites at 85°C.